Magnetic core, magnetic component, and electronic device

By using soft magnetic particles with specific particle size distribution in the magnetic core, the problem that it is difficult to increase the density of the powdered magnetic core during molding is solved, and the effect of improving the DC superposition characteristics of the magnetic core and reducing the core loss is achieved.

CN119920561APending Publication Date: 2025-05-02TDK CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411519042.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-28
Filing Date
2024-10-29
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

It is difficult to increase the density of existing powdered magnetic cores during molding, resulting in large core loss.

Method used

The density and performance of the core is improved by using a core design containing soft magnetic particles of a specific particle size distribution, where the particle size distribution and spacing of large and small particles are within a specific range.

Benefits of technology

The effect of improving the DC superposition characteristics of the magnetic core and reducing the core loss is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920561A_ABST
    Figure CN119920561A_ABST
Patent Text Reader

Abstract

A magnetic core includes soft magnetic particles. V10 represents the value of D10 in the particle size distribution of the soft magnetic particles on a volume basis; v50 represents the value of D50 in the particle size distribution of the soft magnetic particles on a volume basis; when the value of D50 in the number-based particle size distribution of the soft magnetic particles is N50, the soft magnetic particles include large particles having a particle size of (0.5 * V50) or more and small particles having a particle size of (2 * N50) or less. When L is the distance from a certain small particle to a large particle closest to the small particle, and L50 is the median value of L calculated for all the small particles, L50 is within a specific range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnetic core, a magnetic component and electronic equipment. Background Art

[0002] Patent Document 1 describes an inductor formed by integrally molding a powder core obtained by compacting metal magnetic powder and a coil portion.

[0003] When metal magnetic powder is used in a powder core, the core loss tends to increase. By using amorphous alloy powder as the metal magnetic powder, the core loss is reduced. However, it is difficult to increase the density of the powder core during molding.

[0004] Patent Documents 2 and 3 describe the use of a mixture of crystalline alloy magnetic powder and amorphous alloy magnetic powder.

[0005] Patent Document 4 describes that by using an amorphous soft magnetic powder having a high average practical sphericity, it is possible to provide an inductor or the like having lower loss than conventional ones.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-309024

[0009] Patent Document 2: Japanese Patent Application Publication No. 2004-197218

[0010] Patent Document 3: Japanese Patent Application Publication No. 2004-363466

[0011] Patent Document 4: Japanese Patent No. 5110660 Summary of the invention

[0012] Technical problem to be solved by the invention

[0013] The object of the present invention is to obtain a magnetic core having improved DC superposition characteristics and improved core loss.

[0014] Means for solving technical problems

[0015] In order to achieve the above object, one aspect of the present invention provides a magnetic core of an exemplary embodiment, which is a magnetic core containing soft magnetic particles, wherein:

[0016] When the value of D10 in the particle size distribution (unit: μm) of the soft magnetic particles on a volume basis is V10, the value of D50 in the particle size distribution of the soft magnetic particles on a volume basis is V50, and the value of D50 in the particle size distribution of the soft magnetic particles on a number basis is N50,

[0017] The soft magnetic particles include large particles with a particle size of (0.5×V50) or more and small particles with a particle size of (2×N50) or less.

[0018] When the distance from a certain small particle to the largest particle closest to the small particle is set as L, and the median value of L calculated for all small particles is set as L50,

[0019] Satisfies (2×N50)≤L50≤(0.5×V10+3.0).

[0020] In order to achieve the above object, another aspect of the present invention relates to a magnetic core of an exemplary embodiment, which is a magnetic core containing soft magnetic particles, wherein:

[0021] When the value of D10 in the particle size distribution of the soft magnetic particles based on volume is V10, the value of D50 in the particle size distribution of the soft magnetic particles based on volume is V50, and the value of D50 in the particle size distribution of the soft magnetic particles based on number is N50,

[0022] The soft magnetic particles include large particles with a particle size of (0.5×V50) or more and small particles with a particle size of (2×N50) or less.

[0023] When the distance from a certain small particle to the largest particle closest to the small particle is set as L, and the median value of L calculated for all small particles is set as L50,

[0024] Satisfies: (2×N50)≤L50≤(0.5×V10).

[0025] The following description also applies to the magnetic core according to any of the above-described exemplary embodiments.

[0026] Alternatively, at least a portion of the soft magnetic particles may be composed of a composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f (atomic ratio) means,

[0027] X1 is one or more selected from Co and Ni,

[0028] X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements,

[0029] X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W,

[0030] Satisfies 0≤p≤0.5,

[0031] 2.00≤a≤20.00,

[0032] 0.00≤b≤14.00,

[0033] 0.00≤c≤15.00,

[0034] 0.00≤d≤5.00,

[0035] 0.00≤e≤3.00,

[0036] 0.00≤f≤9.00, and

[0037] 70.00≤100-(a+b+c+d+e+f)≤96.00.

[0038] V10 may be greater than or equal to 3.0 μm and less than or equal to 20.0 μm.

[0039] V50 may be 8.0 μm or more and 40.0 μm or less.

[0040] At least a part of the soft magnetic particles may contain Fe, Co and / or Ni.

[0041] A magnetic component according to an exemplary embodiment of the present invention includes any one of the above-described magnetic cores.

[0042] An electronic device according to an exemplary embodiment of the present invention includes any one of the above-described magnetic cores. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a SEM image of the cross section of sample number 5.

[0044] Figure 2 It is a graph showing the distribution of various lengths.

[0045] Figure 3 This is an example of a graph obtained by X-ray crystal structure analysis.

[0046] Figure 4 is through Figure 3An example of a pattern obtained by performing profile fitting on a graph of . DETAILED DESCRIPTION

[0047] Next, embodiments of the present invention will be described.

[0048] (First Embodiment)

[0049] The magnetic core of the present embodiment includes soft magnetic particles. The soft magnetic particles include at least large particles and small particles described below.

[0050] The method for observing the soft magnetic particles contained in the magnetic core is not particularly limited. For example, a method of observing the cross section of the magnetic core using SEM or TEM can be cited. In addition, the cross section obtained by cutting the magnetic core can also be ground.

[0051] The size of the observation range in the cross section of the magnetic core is not particularly limited. The observation range is set in a manner such that the soft magnetic particles contained in the observation range add up to more than 10,000. It is preferred to set one observation range or multiple continuous observation ranges. However, multiple observation ranges can also be set at mutually separated locations.

[0052] The magnification and resolution when observing the cross section of the magnetic molded body are not particularly limited. The magnification may be 500 to 3000 times, and the resolution may be 2560×1920 or more.

[0053] The particle size of all soft magnetic particles included in each observation range is measured. The particle size of each soft magnetic particle is the Heywood diameter. The Heywood diameter refers to the projected area circle equivalent diameter. The Heywood diameter of the soft magnetic particles in this embodiment is (4S / π) when the area of ​​the soft magnetic particles in the cross section is set to S. 1 / 2 .

[0054] The volume of each soft magnetic particle is calculated by assuming that the shape of each soft magnetic particle is spherical. That is, the volume of each soft magnetic particle is calculated by assuming that the particle size of each soft magnetic particle is d (πd 3 The volume of all the soft magnetic particles is calculated by the above method.

[0055] By the above method, the particle diameter and volume of all the soft magnetic particles included in each observation range are calculated.

[0056] Next, the particle size distribution of the soft magnetic particles based on number is calculated based on the particle size of each soft magnetic particle calculated by the above method. The particle size distribution of the soft magnetic particles based on volume is calculated based on the particle size and volume of each soft magnetic particle calculated by the above method.

[0057] The calculation of the particle size distribution requires setting intervals. In this embodiment, 100 intervals are set according to the following formula. Let i = 1, 2, 3 ... 100, x i is equal to i, y i is the average particle size in interval i (unit: μm). In addition, exp(X)=e X , e is the base of natural logarithms.

[0058] y i =0.02×exp(x i ×0.085)

[0059] For example, the average particle size of the first interval from the smallest is 0.02×e 0.085 =0.022μm. Similarly, the average particle size of the second interval is 0.02×e 0.17 =0.024 μm, and the average particle size of the 50th interval is 0.02×e 4.25 =1.402μm, the average particle size of the 100th interval is 0.02×e 8.5 =98.295μm.

[0060] Then, the volume-based particle size distribution of the soft magnetic particles and the number-based particle size distribution of the soft magnetic particles are calculated using the intervals set by the above method. An example of the results is shown in Figure 2 . Figure 2 (1) is a graph showing the particle size distribution of soft magnetic particles on a volume basis. Figure 2 (2) is a graph showing the particle size distribution of soft magnetic particles on a number basis. In the graphs of (1) and (2), the horizontal axis represents the particle size.

[0061] In this embodiment, the value of D10 in the particle size distribution (unit: μm) of the soft magnetic particles based on volume is set to V10; the value of D50 in the particle size distribution of the soft magnetic particles based on volume is set to V50; and the value of D50 in the particle size distribution of the soft magnetic particles based on number is set to N50. In the following, unless otherwise specified, the unit of particle size and particle size distribution is μm. Figure 2 The position of V10 and the position of N50 are shown in FIG. 1 . In addition, D10 and D50 in the particle size distribution of soft magnetic particles based on volume refer to the particle size when the cumulative relative frequency based on volume is 10% (0.10) and 50% (0.50). D50 in the particle size distribution of soft magnetic particles based on number refers to the particle size when the cumulative relative frequency based on number is 50% (0.50).

[0062] Then, the soft magnetic particles with a particle size of (0.5×V50) or more are set as large particles, and the soft magnetic particles with a particle size of (2×N50) or less are set as small particles. The soft magnetic particles of this embodiment include large particles and small particles. The soft magnetic particles of this embodiment may also include particles that are not classified as large particles or small particles, that is, particles with a particle size greater than (2×N50) and less than (0.5×V50).

[0063] Compared with the case where the distance between large particles and small particles is distributed outside a specific range, the magnetic core of this embodiment can improve the DC superposition characteristics and reduce the core loss by distributing the distance between large particles and small particles within a specific range.

[0064] The distance from a certain small particle to the large particle closest to the small particle is defined as L. Specifically, the distance from the surface of a certain small particle to the surface of the largest particle closest to the small particle is measured, and this distance is defined as L.

[0065] For all small particles within the observation range, L is measured. Then, the distribution of L is calculated. At this time, 100 intervals are set by the same method as above. In addition, the above particle size is appropriately replaced with distance.

[0066] Then, the distribution of L is calculated using the intervals set by the above method. An example of the result is shown in Figure 2 . Figure 2 (3) is a graph showing the distribution of L. In the graph of (3), the horizontal axis represents L.

[0067] Set the median value of L to L50. Figure 2 The position of L50 is shown in FIG. Then, the structure of the magnetic core of the present embodiment satisfies (2×N50)≤L50≤(0.5×V10+3.0). It may also satisfy (2×N50)≤L50≤(0.5×V10+2.5). In the following description, “0.5×V10+3.0” is sometimes simply described as “0.5×V10+3”.

[0068] When L50 is too small, the small particles are dispersed in the magnetic core without aggregation. As a result, the small particles are easily distributed in a manner that forms a layer of about one layer near the large particles (grain boundary between two large particles). In other words, a layer of small particles having a thickness equal to the diameter of the small particles is easily formed near the large particles (grain boundary between two large particles).

[0069] When L50 is too large, a plurality of small particles are aggregated and exist in the magnetic core, and as a result, a large number of small particles aggregated near large particles (grain boundaries between two large particles) are included.

[0070] By making L50 within the above range, small particles in the magnetic core tend to be moderately aggregated at a position away from large particles to a certain extent. On the other hand, small particles are difficult to be distributed near large particles (grain boundaries between two large particles) in a manner of forming a layer or so. As a result, by making small particles moderately included between large particles, magnetic saturation is easily prevented, and DC superposition characteristics are easily improved. Furthermore, core loss (core loss) is reduced.

[0071] When the structure of the core satisfies (2×N50)≤L50≤(0.5×V10+3), the DC superposition characteristics of the core are improved and the core loss is reduced compared to the case where the conditions are substantially the same except that L50 is too small and the case where the conditions are substantially the same except that L50 is too large. In particular, the core loss is reduced compared to the case where the conditions are substantially the same except that L50 is too large.

[0072] The values ​​of V10, V50, and N50 are not particularly limited. For example, V10 may be 2.0 μm to 25.0 μm, V50 may be 4.0 μm to 50.0 μm, and N50 may be 0.2 μm to 5.0 μm. Of course, V10≤V50 is satisfied.

[0073] V10 may be 3.0 μm or more and 20.0 μm or less, and V50 may be 8.0 μm or more and 40.0 μm or less.

[0074] The value of L50 is not particularly limited, but may be, for example, 0.8 μm or more and 8.0 μm or less.

[0075] The total area ratio of the soft magnetic particles to the entire cross section of the magnetic core is not particularly limited. For example, it can be 70% to 95%. If the total area ratio is too small, the filling rate of the soft magnetic particles in the magnetic core is too low, so the magnetic permeability is likely to decrease.

[0076] The total area ratio of the large particles to the entire cross section may be 70% or more. The total area ratio of the small particles may be 70% or more.

[0077] The average circularity of the large particles constituting the magnetic core may be greater than 0.50. Preferably, it is greater than 0.85, and more preferably, it is greater than 0.90. The higher the circularity of the large particles, the easier it is to improve the filling property of the soft magnetic particles in the magnetic core. The average circularity of the small particles constituting the magnetic core may also be greater than 0.50. Preferably, it is greater than 0.85, and more preferably, it is greater than 0.90. The higher the circularity of the small particles, the easier it is to improve the filling property of the soft magnetic particles in the magnetic core. The higher the circularity, the easier it is to improve the filling property of the soft magnetic particles in the magnetic core, and this is the same for large particles and small particles.

[0078] In addition, the large particles and / or small particles of the present embodiment may also have a coating on the surface. The coating may also be an insulating coating. The type of the coating is not particularly limited, as long as it is formed by a coating commonly used in the technical field. Examples include iron oxides, phosphates, silicates (water glass), soda lime glass, borosilicate glass, lead glass, aluminosilicate glass, borate glass, sulfate glass, etc. Examples of phosphates include magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate. Examples of silicates include sodium silicate. In addition, the thickness of the coating is not particularly limited. For example, it may be on average more than 5 nm and less than 100 nm.

[0079] In addition, the magnetic core of the present embodiment may also contain resin in addition to the soft magnetic particles. The type of resin is not particularly limited. For example, silicone resin or epoxy resin is exemplified. The content of the resin in the magnetic core is also not particularly limited. For example, relative to 100 parts by mass of soft magnetic particles, it can be more than 1.0 parts by mass and less than 5.0 parts by mass, or it can be more than 1.5 parts by mass and less than 3.5 parts by mass. In the case of too much resin, the filling rate of the soft magnetic particles is easily reduced, and the magnetic permeability is easily reduced. If the filling rate of the soft magnetic particles is increased in order to increase the magnetic permeability, the DC superposition characteristics are easily reduced.

[0080] Furthermore, the portion other than the magnetic body (eg, soft magnetic particles) in the cross section of the magnetic core may be occupied by the resin, or by the resin and the voids.

[0081] There is no particular restriction on the fine structure of the soft magnetic particles. For example, the soft magnetic particles may have a structure containing amorphous matter or a structure composed of crystals. The soft magnetic particles (especially large particles) may also have a nano heterogeneous structure. The nano heterogeneous structure refers to a structure containing initial microcrystals with an average crystal particle size of 0.3 nm or more and 10 nm or less in amorphous matter. When the filling rate is roughly the same, when the soft magnetic particles (especially large particles) have a nano heterogeneous structure, the relative magnetic permeability is improved compared with the case where the soft magnetic particles (especially large particles) have a structure composed only of amorphous matter. Further, the soft magnetic particles (especially large particles) may also have a structure composed of crystals, and the average crystal particle size is 1 nm or more and 30 nm or less and the crystal particle size is a structure (nanocrystalline structure) of 100 nm or less at most. When the filling rate is roughly the same, when the soft magnetic particles (especially large particles) have a nano crystalline structure, the relative magnetic permeability of the magnetic core is further improved. In addition, in soft magnetic particles containing crystals, especially nano crystals, one particle usually contains a plurality of crystals. That is, the particle size of the soft magnetic particles is different from the crystal particle size. The method for calculating the crystal particle size is not particularly limited, and an example thereof is a method for calculating the crystal particle size by observing crystals using a TEM.

[0082] And the nanocrystal that comprises in the soft magnetic particle (particularly macroparticle) can also be Fe-based nanocrystal.Fe-based nanocrystal refers to that average crystal grain size is nano-level (specifically more than 0.1nm and less than 100nm) and the crystal structure of Fe is the crystallization of bcc (body-centered cubic lattice structure).The calculation method of the average crystal grain size of Fe-based nanocrystal is not particularly limited.For example, can enumerate by using TEM to observe and calculate the method for crystal grain size.In addition, confirming that crystal structure is the method for bcc is not particularly limited either.For example, can enumerate by using the electron diffraction pattern that TEM is obtained to analyze and confirm the method.

[0083] In the present embodiment, the average crystal grain size of the Fe-based nanocrystals may also be 1 to 30 nm. The saturation flux density of the soft magnetic particles having such a structure composed of Fe-based nanocrystals tends to be high, and the coercive force tends to be low. That is, the soft magnetic properties are easily improved. That is, by including the soft magnetic particles, it is easy to make the magnetic core (especially the magnetic molded body) have low coercive force and high relative permeability. Moreover, because the saturation flux density of the magnetic core (especially the magnetic molded body) containing the soft magnetic particles increases, the DC superposition characteristics of the magnetic core (especially the magnetic molded body) are improved. Thus, by using soft magnetic particles having a structure composed of Fe-based nanocrystals, it is easy to improve the characteristics of the magnetic core (especially the magnetic molded body).

[0084] The method for confirming the fine structure of soft magnetic particles is not particularly limited. For example, it is possible to confirm whether the soft magnetic particles have a structure consisting of amorphous or a structure consisting of crystal by cross-sectional observation based on TEM. Specifically, it is possible to confirm by analyzing the halo pattern derived from amorphous according to the electron diffraction pattern obtained by TEM. In addition, even when two or more soft magnetic particles with different fine structures are included in the magnetic core, it is also possible to confirm the fine structure of each soft magnetic particle by cross-sectional observation based on TEM.

[0085] The composition of the soft magnetic particles is not particularly limited. In addition, the composition of the soft magnetic particles described below may be the average composition of all the soft magnetic particles contained in the magnetic core.

[0086] At least a portion of the soft magnetic particles may be composed of a composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f (atomic ratio) means,

[0087] X1 may be one or more selected from Co and Ni,

[0088] X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements,

[0089] X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W,

[0090] It can also satisfy 0≤p≤0.5,

[0091] 2.00≤a≤20.00,

[0092] 0.00≤b≤14.00,

[0093] 0.00≤c≤15.00,

[0094] 0.00≤d≤5.00,

[0095] 0.00≤e≤3.00,

[0096] 0.00≤f≤9.00, and

[0097] 70.00≤100-(a+b+c+d+e+f)≤96.00.

[0098] A magnetic core including soft magnetic particles having a composition within the above range is likely to have excellent DC superposition characteristics.

[0099] The composition of at least a portion of the soft magnetic particles may be the average composition of the large particles.

[0100] The method for analyzing the composition of the soft magnetic particles is not particularly limited. For example, it can be confirmed by ICP analysis. In addition, for the cross section of the molded body containing the soft magnetic particles, SEM-EDS or EPMA etc. can also be used for analysis.

[0101] Next, each component of the soft magnetic particles will be described in detail.

[0102] X1 is one or more selected from Co and Ni. It may also contain soft magnetic particles with 0≤p≤0.5. A magnetic core containing soft magnetic particles whose content ratio of Fe is greater than the total content ratio of Co and Ni is likely to have excellent DC superposition characteristics.

[0103] The soft magnetic particles may contain a content (a) of B satisfying 2.00≤a≤20.00. The magnetic core containing the soft magnetic particles having a content of B within the above range is likely to have excellent DC superposition characteristics.

[0104] The soft magnetic particles may be included in which the P content (b) satisfies 0.00≤b≤14.00. The magnetic core including the soft magnetic particles having the P content within the above range is likely to have excellent DC superposition characteristics.

[0105] The soft magnetic particles may contain Si content (c) satisfying 0.00≤c≤15.00. The magnetic core containing the soft magnetic particles having Si content within the above range is likely to have excellent DC superposition characteristics.

[0106] The soft magnetic particles may be included in which the content (d) of C satisfies 0.00≤d≤5.00. The magnetic core including the soft magnetic particles having a C content within the above range is likely to have excellent DC superposition characteristics.

[0107] The soft magnetic particles may be included in which the content (e) of X2 satisfies 0.00≤e≤3.00. The magnetic core including the soft magnetic particles in which the content of X2 is within the above range is likely to have excellent DC superposition characteristics.

[0108] The soft magnetic particles may be included in which the content (f) of X3 satisfies 0.00≤f≤9.00. The magnetic core including the soft magnetic particles in which the content of X3 is within the above range is likely to have excellent DC superposition characteristics.

[0109] It may also contain soft magnetic particles satisfying 70.00≤100-(a+b+c+d+e+f)≤96.00. The total content of Fe and X1 in the soft magnetic particles is 70.00at% or more and 96.00at% or less. The magnetic core containing soft magnetic particles having a total content of Fe and X1 within the above range is likely to become a magnetic core having excellent DC superposition characteristics.

[0110] The soft magnetic particles may also contain oxygen. Moreover, the oxygen content relative to 100% by mass of the soft magnetic particles may be between 0 ppm and 10,000 ppm on a mass basis. A magnetic core containing soft magnetic particles having an oxygen content within the above range is likely to have excellent DC superposition characteristics.

[0111] In addition, the soft magnetic particles may contain elements other than Fe, X1, B, P, Si, C, X2 and X3 as inevitable impurities within a range that does not have a significant effect on the performance. The oxygen content is as described above. In addition, the elements other than oxygen in the inevitable impurities may be contained in an amount of 0.1% by mass or less relative to 100% by mass of the soft magnetic particles.

[0112] At least a part of the soft magnetic particles may contain Fe, Co and / or Ni as a main component.

[0113] Containing Fe, Co and / or Ni as main components means that the total content of Fe, Co and / or Ni in the soft magnetic particles is 50 at % or more and 100 at % or less.

[0114] In addition, when Fe, Co and / or Ni are contained as main components, the types of elements other than the main components are not particularly limited, and examples thereof include Cr, Al, Si, B, P, C, O, Nb, Zr, Ta, Mn, V, Cu, S and the like.

[0115] In the case where soft magnetic particles (especially large particles) have a structure composed of nanocrystals, as the composition of the soft magnetic particles, Fe-Si-B-Nb-Cu system, Fe-BP-Si-Cu system, Fe-BP-Si-Nb-Cr system, etc., which are easy to have a structure composed of nanocrystals, are exemplified.

[0116] In the manufacturing method of the magnetic core described later, when the soft magnetic powder containing the soft magnetic particles having the above composition is heat-treated, Fe-based nanocrystals are easily precipitated in the soft magnetic particles. In other words, the soft magnetic powder having the above composition is easy to be used as the starting material of the soft magnetic powder having the soft magnetic particles that precipitate Fe-based nanocrystals.

[0117] When Fe-based nanocrystal is separated out in soft magnetic particles by heat treatment, the soft magnetic particles before the heat treatment can have the structure that is only made of amorphous, or can have the nano heterostructure that initial microcrystal is present in amorphous. In addition, the average grain size of initial microcrystal can also be below 10nm above 0.3nm.

[0118] In the case where soft magnetic particles (especially large particles) have a structure composed of amorphous substances, as the composition of the soft magnetic particles, examples include Fe-Co-BP-Si-Cr system, Fe-Co-BP-Si system, Fe-B-Si-C-Cr system, Fe-B-Si-C system, etc., which are easy to have a structure composed of amorphous substances.

[0119] In the case where soft magnetic particles (especially large particles) have a structure composed of crystals, examples of the composition of the soft magnetic particles include Fe-based, Fe-Co-based, Fe-Si-based, Fe-Co-Si-based, Fe-Si-Cr-based, Fe-Co-Si-Cr-based, Fe-Si-Al-based, and the like, which are compositions that easily have a structure composed of crystals.

[0120] The composition of the soft magnetic particles (particularly small particles) is not particularly limited and may contain Fe, Co and / or Ni as main components.

[0121] By making the soft magnetic particles (particularly small particles) have the above composition, a high saturation magnetic flux density can be easily obtained, and a magnetic core having high magnetic characteristics can be easily produced.

[0122] The method for manufacturing the magnetic core of the present embodiment will be described below, but the method for manufacturing the magnetic core is not limited to the method described below.

[0123] First, a soft magnetic powder including the soft magnetic particles of the present embodiment is prepared. The soft magnetic powder of the present embodiment can be obtained by mixing a soft magnetic powder that will mostly become large particles and a soft magnetic powder that will mostly become small particles.

[0124] The soft magnetic powder that is ultimately mostly large particles can be produced by, for example, water atomization or gas atomization. The gas atomization is described below. The water atomization is the same as the gas atomization except that the high-pressure gas sprayed toward the molten metal is replaced with water.

[0125] In the gas atomization method, the molten metal obtained by melting the raw material metal is powdered by the gas atomization method to produce soft magnetic powder. The composition of the molten metal is set to be the same as the composition of the soft magnetic particles to be finally obtained. At this time, the molten metal drips from a container formed with a discharge port toward a cooling part. The temperature of the molten metal is the injection temperature. There is no particular restriction on the injection temperature. For example, it is 1200°C or more and 1600°C or less. The higher the injection temperature, the easier it is for the average circularity to approach 1, and the easier it is for the average particle size to become smaller.

[0126] In addition, a gas injection nozzle having a gas injection port is arranged in a manner surrounding the above-mentioned discharge port. High-pressure gas (the injection pressure (gas pressure) is a gas of not less than 2.0 MPa and not more than 10 MPa) is injected from the gas injection port toward the molten metal dripping from the discharge port. As a result, the molten metal becomes a plurality of droplets. By controlling the pressure of the high-pressure gas at this time, the particle size of the soft magnetic powder and the shape of the soft magnetic powder can be changed. Specifically, when the injection amount of the molten metal is the same, the higher the pressure of the high-pressure gas, the smaller the particle size of the soft magnetic powder can be obtained. That is, the particle size of the soft magnetic powder or the shape of the soft magnetic powder can be changed according to the ratio of the pressure of the high-pressure gas to the injection amount of the molten metal.

[0127] As the gas injected from the gas injection port, an inert gas such as nitrogen, argon, helium, or a reducing gas such as ammonia decomposition gas is preferred. Alternatively, air may be used when the molten metal is not easily oxidized.

[0128] The shape of the cooling part where the molten metal is dripped is not particularly limited. For example, it can also be made into a cylinder with a cooling liquid flow that collides with the molten metal formed inside. In this case, by controlling the injection amount of the molten metal, the high-pressure gas pressure shown above, and the water pressure of the cooling liquid flow, the particle size or average circularity of the large particles in the magnetic core finally obtained can be changed. That is, the particle size or average circularity of the soft magnetic particles is controlled under the balance of the injection amount of the molten metal, the high-pressure gas pressure, and the water pressure of the cooling liquid flow. The injection amount of the molten metal can also be more than 0.5kg / min and less than 4.0kg / min, and the water pressure can also be more than 5.0MPa and less than 20.0MPa. Specifically, the larger the injection amount, the easier it is for the particle size to become larger. In addition, the lower the water pressure, the easier it is for the average circularity of the large particles to approach 1.

[0129] The molten metal discharged into the coolant flow collides with the coolant flow, further breaks, refines, changes shape, cools and solidifies, and becomes a solid soft magnetic powder. The soft magnetic powder discharged together with the coolant is separated into the coolant in an external storage tank and taken out. In addition, the type of coolant is not particularly limited. For example, cooling water can be used.

[0130] The obtained soft magnetic powder may also be subjected to heat treatment. The conditions of the heat treatment are not particularly limited. For example, the heat treatment may be performed at 400 to 700° C. for 0.1 to 10 hours. By performing the heat treatment, in the case where the fine structure of the soft magnetic particles is a nano-heterogeneous structure having only an amorphous structure or an initial microcrystal existing in an amorphous structure, the fine structure of the soft magnetic particles tends to become a structure composed of nanocrystals.

[0131] The method for producing the soft magnetic powder that is ultimately mostly small particles is not particularly limited, and can be produced by various powdering methods such as a liquid phase method, a spray pyrolysis method, and a melting method.

[0132] The average particle size of the soft magnetic powder, which is mostly small particles, can be controlled by appropriately removing coarse powder and / or fine powder using an air classifier.

[0133] Next, a method for confirming the fine structure of the soft magnetic particles contained in each powder will be described.

[0134] The method for confirming the fine structure of the soft magnetic particles contained in each powder before molding described below is not particularly limited. TEM can be used in the same manner as the method for confirming the fine structure of the soft magnetic particles contained in the magnetic core.

[0135] When confirming the fine structure of the soft magnetic particles contained in each powder before molding described later, it can be confirmed by XRD. When calculating the crystal grain size contained in the soft magnetic particles, the crystal grain size can also be calculated by analyzing the half width obtained by XRD and evaluating the crystallite size.

[0136] In the case where the soft magnetic particles have a structure consisting only of amorphous or nano-heterogeneous structures, the amorphization rate described below is 85% or more. In the case where the soft magnetic particles have a structure consisting of crystals, the amorphization rate described below is less than 85%. In addition, it can be confirmed by XRD that the crystal structure of Fe is bcc.

[0137] Next, a method for confirming the fine structure of soft magnetic particles using XRD will be described in detail.

[0138] Soft magnetic particles having an amorphization rate X of 85% or more represented by the following formula (1) are regarded as having a structure consisting only of amorphous materials or a nano-heterostructure, and soft magnetic particles having an amorphization rate X of less than 85% are regarded as having a structure consisting of crystals.

[0139] X=100-(Ic / (Ic+Ia)×100)……(1)

[0140] Ic: Crystalline scattering integrated intensity

[0141] Ia: Amorphous scattering integrated intensity

[0142] The amorphous ratio X is obtained by performing X-ray crystal structure analysis on the soft magnetic particles using XRD to identify the phase, reading the peak of Fe or the compound after crystallization (Ic: integrated intensity of crystalline scattering, Ia: integrated intensity of amorphous scattering), and calculating the crystallization ratio based on the peak intensity, which is calculated according to the above formula (1). The calculation method is further described in detail below.

[0143] The soft magnetic particles of this embodiment were analyzed by X-ray crystal structure analysis using XRD, and the Figure 3 The peak shape is fitted using the Lorentz function of the following formula (2), and we get Figure 4 The crystal component pattern α showing the integrated intensity of crystalline scattering is shown in FIG. c , amorphous component pattern α representing the integrated intensity of amorphous scattering a and the pattern α that combines them c+aThe amorphization rate X is calculated by the above formula (1) based on the crystalline scattering integrated intensity and the amorphous scattering integrated intensity of the obtained pattern. In addition, the measurement range is set to the range of diffraction angle 2θ=30° to 60° in which the halo originating from the amorphous can be confirmed. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated using the Lorentz function is within 1%.

[0144]

[0145] h: peak height

[0146] u: peak position

[0147] w: half width

[0148] b: background height

[0149] In addition, the above-mentioned soft magnetic powders may also be coated at this time. The method for forming the coating is not particularly limited.

[0150] Next, a magnetic core is made using each of the soft magnetic powders. First, each of the soft magnetic powders is weighed. Hereinafter, the soft magnetic powder that eventually becomes mostly large particles is referred to as powder A; the soft magnetic powder that eventually becomes mostly small particles is referred to as powder B. There is no particular restriction on the mixing ratio of each soft magnetic powder. For example, the proportion of powder A can be 30% by mass or more and 90% by mass or less. The proportion of powder B can be 10% by mass or more and 70% by mass or less.

[0151] In addition to powder A and powder B, powder C having an average particle size between powder A and powder B may be used. Powder C is likely to become particles that are mostly neither large particles nor small particles in the end. The composition and fine structure of powder C are not particularly limited. It may be the same as powder A, the same as powder B, or different from both powder A and powder B. In the case of using powder C having an average particle size between powder A and powder B in addition to powder A and powder B, the total ratio of powder B and powder C may be 10% by mass or more and 70% by mass or less.

[0152] Next, the weighed powder B is agglomerated. Specifically, after powder B is mixed with a resin, the powder B obtained by mixing with the resin is filled into a mold and compressed. Powder B is set to 100 parts by mass, and the amount of resin added can be more than 0.1 parts by mass and less than 0.3 parts by mass. The less the amount of resin added, the more difficult it is for powder B to agglomerate. In addition, the higher the pressure value during compression, the more continuous the agglomeration of powder B will be, and the easier it is for the L50 of the magnetic core finally obtained to become larger. The pressure value during compression can be, for example, more than 10 MPa and less than 1600 MPa, can be more than 10 MPa and less than 1000 MPa, or can be more than 40 MPa and less than 600 MPa.

[0153] Next, powder A, condensed powder B and resin are kneaded to prepare a resin mixture. When powder C is used, powder C is also kneaded. The content of the soft magnetic powder in the resin mixture is set to 100 parts by mass, and the content of the resin can be more than 1.0 parts by mass and less than 5.0 parts by mass, or more than 1.5 parts by mass and less than 3.5 parts by mass. The less the amount of resin, the more difficult it is to compress and mold the soft magnetic powder. In addition, the strength of the magnetic core obtained by compression molding the soft magnetic powder is more likely to decrease, and it is more likely to become difficult to handle.

[0154] The agglomerated powder B is crushed to some extent by kneading. The higher the pressure value during compression, the harder it is to crush the powder B, and the lower the pressure value during compression, the easier it is to crush the powder B.

[0155] Then, the obtained resin mixture is filled into a mold and compression molded to obtain a magnetic core. The molding pressure during compression molding is not particularly limited. For example, it can be 98 MPa or more and 981 MPa or less. In addition, the resin contained in the obtained magnetic core can also be thermally cured.

[0156] The composition and fine structure of the soft magnetic particles contained in the soft magnetic powder before compression molding and the composition and fine structure of the soft magnetic particles contained in the magnetic core after compression molding are usually the same.

[0157] As mentioned above, the magnetic core (magnetic molded body) of this embodiment has been described, but the magnetic core (magnetic molded body) of the present invention is not limited to the above-mentioned embodiment.

[0158] In addition, the use of the magnetic core of the present invention is not particularly limited. For example, coil components (magnetic components) such as inductors, chokes, and transformers can be cited. Electronic devices such as DC-DC converters using the magnetic core of the present invention can also be cited.

[0159] (Second Embodiment)

[0160] Next, a second embodiment will be described. Matters not particularly described are the same as those of the first embodiment.

[0161] In the present embodiment, the structure of the magnetic core satisfies (2×N50)≤L50≤(0.5×V10).

[0162] When the structure of the core satisfies (2×N50)≤L50≤(0.5×V10), the DC superposition characteristics of the core are improved and the core loss is reduced compared to the case where the conditions are substantially the same except that L50 is too small and the case where the conditions are substantially the same except that L50 is too large. In particular, the DC superposition characteristics are improved compared to the case where the conditions are substantially the same except that L50 is too large.

[0163] In the second embodiment, the pressure value when the powder B mixed with the resin is filled into a mold and compressed may be, for example, 10 MPa to 1000 MPa, or 40 MPa to 600 MPa.

[0164] [Example]

[0165] Hereinafter, the present invention will be described based on more detailed examples, but the present invention is not limited to these examples.

[0166] (Experimental Example 1)

[0167] In Experimental Example 1, a powder A, which is mostly large particles, was produced by gas atomization. The composition of the powder A was set to be a Fe-Co-BP-Si-Cr system composition. Specifically, the composition was set to be 57.4Fe-24.6Co-11.0B-3.0P-3.0Si-1.0Cr in terms of atomic ratio.

[0168] Regarding the conditions of the gas atomization method, the pressure of the high-pressure gas is set to 2.0 MPa or more and 10 MPa or less; the ejection rate of the molten metal is set to 0.5 kg / min or more and 4.0 kg / min or less. The atomization conditions and classification conditions are appropriately controlled so that the median particle size (D50) of the obtained powder A on a volume basis becomes 20 μm. In addition, in the classification of the powder A, at least sieve classification using a sieve with a mesh size of 63 μm is performed.

[0169] By ICP analysis, it was confirmed that the composition of the master alloy of each sample was substantially the same as the composition of the powder A. It was confirmed that the volume-based median particle size (D50) of the obtained powder A was 20 μm. The volume-based median particle size was measured by laser diffraction using a dry particle size distribution measuring device.

[0170] Carbonyl iron powder was used as powder B, which was mostly small particles. That is, the composition of the soft magnetic particles contained in powder B was set to a composition containing only Fe. In addition, the coarse powder and / or fine powder were appropriately removed by using an air flow classifier, so that the median particle size (D50) of powder B was 0.8 μm based on volume. By ICP analysis, it was confirmed that the composition of powder B was the target composition. Using a dry particle size distribution measuring device, it was confirmed by laser diffraction that the median particle size (D50) of the obtained powder B based on volume was 0.8 μm.

[0171] Each powder was subjected to X-ray diffraction measurement (XRD) to measure the amorphization rate X. When the amorphization rate X was 85% or more, it was assumed to have a structure consisting of amorphous. When the amorphization rate X was less than 85% and the average crystal grain size was less than 100 nm, it was assumed to have a structure consisting of nanocrystals. When the amorphization rate X was less than 85% and the average crystal grain size was greater than 100 nm, it was assumed to have a structure consisting of crystals. In Experimental Example 1, it was confirmed that all powders A had a structure consisting of amorphous, and all powders B had a structure consisting of crystals.

[0172] Next, powder B is agglomerated. First, powder B and epoxy resin are mixed. The amount of epoxy resin added to powder B is set to 0.3 parts by mass relative to 100 parts by mass of powder B. Next, 1 g of powder B mixed with epoxy resin is filled into a cylindrical mold with a diameter of 8 mm Φ. Next, it is agglomerated by compressing at the pressure value shown in Table 1. In the case of producing more than 1 g of agglomerated powder B, the above steps are repeated multiple times. In addition, in sample number 1, powder B is not agglomerated.

[0173] Next, powder A, condensed powder B, and epoxy resin are kneaded to obtain a resin mixture. In addition, in sample number 1, powder A, powder B, and epoxy resin are kneaded to obtain a resin mixture. The mixing ratio of powder A and powder B is set to 80:20 on a mass basis. The total amount of powder A and powder B is set to 100 parts by mass, and the content of epoxy resin is set to 2.0 parts by mass to 3.0 parts by mass. The content of epoxy resin is controlled so that the relative magnetic permeability μ of the final magnetic core becomes 30.

[0174] Next, the resin mixture is filled into a ring-shaped mold and press-molded to obtain a ring-shaped molded body. The molding pressure is appropriately controlled within a range of 98 MPa to 981 MPa so that the relative magnetic permeability μ of the finally obtained magnetic core becomes 30.

[0175] Then, the epoxy resin contained in the obtained molded body was thermally cured to obtain a magnetic core. The heat treatment conditions were set at 180° C. for 60 minutes. The dimensions of the magnetic core were set to an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a thickness of 2.5 mm.

[0176] For the magnetic core of each sample, a cross section cut parallel to the molding direction (height direction) was observed using SEM (SU-5000 manufactured by HITACHI HIGH-TECH CORPORATION), and V10, V50, and N50 were calculated by the above method. The results are shown in Table 1. In addition, the SEM image of the cross section in sample number 5 is Figure 1 .

[0177] Furthermore, L50 was calculated by the above method and compared with 2×N50, 0.5×V10, and 0.5×V10+3. The results are shown in Table 1.

[0178] The relative magnetic permeability μ of the toroidal core of each sample was measured by the following method. First, a polyurethane copper wire (UEW wire) was wound around the toroidal core. Then, an LCR meter (4284A manufactured by Agilent Technologies) was used to measure the inductance of the toroidal core at a frequency of 1 MHz without applying a direct current, and the relative magnetic permeability μ was calculated based on the obtained inductance. The results are shown in Table 1.

[0179] Furthermore, in order to evaluate the DC superposition characteristics of the toroidal core of each sample, Isat was measured. For the toroidal core of each sample, the greater the DC current applied, the lower the relative permeability. When the relative permeability of the toroidal core is measured while applying a DC current, the value of the DC current when the relative permeability decreases by 10% from μ is set as Isat. The results are shown in Table 1.

[0180] Furthermore, the Isat of a sample under the same conditions except that the powder B was not agglomerated was used as a reference, and the improvement rate of Isat relative to the Isat of the sample was shown in Table 1. The case where the improvement rate of Isat was 0.1% or more was considered to have good DC superposition characteristics, the case where it was 1.0% or more was considered to have better DC superposition characteristics, the case where it was 5.0% or more was considered to have even better DC superposition characteristics, the case where it was 10.0% or more was considered to have even better DC superposition characteristics, and the case where it was 15.0% or more was considered to have particularly good DC superposition characteristics. The results are shown in Table 1.

[0181] Furthermore, the core loss (core loss) of the toroidal core of each sample was evaluated. Specifically, for each toroidal core, the primary winding was wound 24 times and the secondary winding was wound 12 times. Then, the iron loss was measured at 2.5 MHz, 10 mT, and 20 to 25°C using a BH analyzer (SY-8232 manufactured by Iwasaki Communication Equipment Co., Ltd.).

[0182] Furthermore, the improvement rate of the core loss of the sample under the same conditions except that the powder B was not agglomerated was used as a reference, and the improvement rate of the core loss relative to the core loss of the sample was calculated. The results are shown in Table 1. The improvement rate of the core loss was 5.0% or more, which was considered to be a good improvement rate of the core loss, 10.0% or more, which was considered to be a better improvement rate of the core loss, and 15.0% or more, which was considered to be a particularly good improvement rate of the core loss. The results are shown in Table 1.

[0183]

Table 1

[0184]

[0185] According to Table 1, compared with the comparative example (sample number 1) in which L50 is too small due to not agglomerating the powder B, in each embodiment (sample numbers 2 to 10, 10a to 10d) in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating the powder B, the DC superposition characteristics are improved and the core loss is improved. However, in the comparative example (sample number 10e) in which L50 is too large due to excessive agglomeration of the powder B, compared with sample number 1, the DC superposition characteristics are not sufficiently improved and the core loss is not sufficiently improved.

[0186] Moreover, compared with the embodiments satisfying L50>0.5×V10 (sample numbers 10, 10a~10d), the DC superposition characteristics of the embodiments satisfying (2×N50)≤L50≤(0.5×V10) (sample numbers 2~9) are further improved.

[0187] (Experimental Example 2)

[0188] Sample Nos. 1 and 5 were tested under substantially the same conditions except that the mixing ratio of powder A and powder B was changed. The results are shown in Table 2. In Tables 2 to 22, Isat and core loss are omitted.

[0189]

Table 2

[0190]

[0191] According to Table 2, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in each embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the mixing ratio of powder A and powder B is changed, the DC superposition characteristics are sufficiently improved and the core loss is sufficiently improved.

[0192] (Experimental Example 3)

[0193] Sample Nos. 1 and 5 were run under substantially the same conditions except that the volume-based median diameter (D50) of the powder A was changed. The results are shown in Table 3.

[0194]

Table 3

[0195]

[0196] According to Table 3, compared with the comparative examples with substantially the same conditions except that L50 was too small because the powder B was not agglomerated, in each embodiment where the median particle size (D50) based on volume of the powder A was changed, the DC superposition characteristics were sufficiently improved and the core loss was sufficiently improved by agglomerating the powder B. In particular, in each embodiment where V10 was 3.0 μm or more and 20.0 μm or less and V50 was 8.0 μm or more and 40.0 μm or less, the Isat improvement rate was further improved compared with the embodiments where V10 and V50 were outside the above ranges.

[0197] (Experimental Example 4)

[0198] Sample Nos. 1 and 5 were run under substantially the same conditions except that the volume-based median diameter (D50) of powder B was changed. The results are shown in Table 4.

[0199]

Table 4

[0200]

[0201] According to Table 4, compared with the comparison example with essentially the same conditions except that L50 is too small due to not agglomerating powder B, in each embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the volume-based median particle size (D50) of powder B is changed, the DC superposition characteristics are sufficiently improved and the core loss is sufficiently improved.

[0202] (Experimental Example 5)

[0203] In Experimental Example 5, except that the coating was formed by insulating coating on the powder A, the other conditions were the same as those of Sample Nos. 1 and 5. Specifically, a coating of P-Zn-Al-O oxide glass was formed on the surface of the powder A. The thickness of the coating was 15 nm. The results are shown in Table 5.

[0204]

Table 5

[0205]

[0206] According to Table 5, compared with the comparison example (sample number 43) which has essentially the same conditions except that L50 is too small due to the failure to agglomerate powder B, in the embodiment (sample number 44) in which the DC superposition characteristics are sufficiently improved and the core loss is sufficiently improved even when the coating is formed by insulating coating and the powder B is agglomerated to satisfy (2×N50)≤L50≤(0.5×V10+3).

[0207] (Experimental Example 6)

[0208] The test was carried out under the same conditions as those of Sample Nos. 1 and 5 except that the composition and microstructure of the powder A were changed. The results are shown in Table 6.

[0209] In sample numbers 45 and 46, the composition of powder A was set to 66.8Fe-16.7Co-11.0B-4.5P-1.0Si in terms of atomic ratio. In sample numbers 47 and 48, the composition of powder A was set to 72.7Fe-10.8B-11.6Si-2.7C-2.2Cr in terms of atomic ratio. In sample numbers 49 and 50, the composition of powder A was set to 81.6Fe-13.4B-3.4Si-1.6C in terms of atomic ratio. It was confirmed by XRD that all powders A of sample numbers 45 to 50 had a structure composed of amorphous substances.

[0210] In sample numbers 51 and 52, the composition of powder A is set to 73.5Fe-13.5Si-9.0B-3.0Nb-1.0Cu in terms of atomic ratio. In sample numbers 53 and 54, the composition of powder A is set to 82.0Fe-11.0B-5.0P-1.0Si-1.0Cu in terms of atomic ratio. In sample numbers 55 and 56, the composition of powder A is set to 78.0Fe-9.0B-3.0P-3.0Si-6.0Nb-1.0Cr in terms of atomic ratio. In addition, for powders A of sample numbers 51 to 56, heat treatment is performed after being produced by gas atomization to precipitate nanocrystals with a crystal particle size of less than 30nm. Specifically, the heat treatment is performed at 400 to 650°C for 10 to 60 minutes. It was confirmed by XRD that all powders A of sample numbers 51 to 56 have a structure composed of nanocrystals.

[0211] In sample numbers 57 and 58, the composition of powder A was set to a composition containing substantially only Fe. In sample numbers 59 and 60, the composition of powder A was set to 50.0Fe-50.0Co in atomic ratio. In sample numbers 61 and 62, the composition of powder A was set to 88.0Fe-12.0Si in atomic ratio. In sample numbers 63 and 64, the composition of powder A was set to 83.6Fe-4.4Co-12.0Si in atomic ratio. In sample numbers 65 and 66, the composition of powder A was set to 89.4Fe-8.6Si-2.0Cr. In sample numbers 67 and 68, the composition of powder A was set to 80.5Fe-9.0Co-8.5Si-2.0Cr. In sample numbers 69 and 70, the composition of powder A was set to 73.7Fe-16.4Si-9.9Al. It was confirmed by XRD that all of the powders A of sample numbers 57 to 70 had a structure composed of crystals.

[0212]

Table 6

[0213]

[0214] According to Table 6, compared with the comparison example with essentially the same conditions except that L50 is too small due to not agglomerating powder B, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition and microstructure of powder A are changed, the DC superposition characteristics are sufficiently improved and the core loss is sufficiently improved.

[0215] (Experimental Example 7)

[0216] Sample Nos. 1 and 5 were tested under the same conditions except that the composition of powder A was changed. The composition of powder A was mainly changed in the total content ratio of Fe and Co. The results are shown in Table 7. Regarding Experimental Examples 7 to 12, the description of comparative examples with substantially the same conditions as the samples was omitted except that L50 was too small because powder B was not agglomerated.

[0217]

Table 7

[0218]

[0219] According to Table 7, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0220] In particular, for sample numbers 102 to 117 in which the total content of Fe and Co is 70.00 at% or more and 96.00 at% or less, the improvement rate of core loss is higher than that of sample number 101 in which the total content of Fe and Co is small, and the improvement rate of Isat is higher than that of sample number 118 in which the total content of Fe and Co is large. It is believed that the improvement rate of core loss of sample number 101 is low because the magnetic properties are lower than those of other samples due to the small content of magnetic elements. It is also believed that the improvement rate of Isat of sample number 118 is low because the amorphous nature of powder A is lower than that of other samples, so the magnetic properties of powder A are lower than those of other samples.

[0221] (Experimental Example 8)

[0222] The comparative example and sample number 106 were run under substantially the same conditions as sample number 106 except that powder B was not agglomerated and L50 was too small, but the contents of Fe, Co, and Ni in powder A were changed. The results are shown in Table 8.

[0223]

Table 8

[0224]

[0225] According to Table 8, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0226] In particular, the Isat improvement rates of sample numbers 106, 121 to 125, 127 to 131, and 133 to 136, in which the Fe content is greater than the total content of Co and Ni, are better than those of sample numbers 126, 132, and 137, in which the Fe content is less than the total content of Co and Ni. It is believed that the Isat improvement rates of sample numbers 126, 132, and 137 are low because the magnetic properties are lower than those of other samples.

[0227] (Experimental Example 9)

[0228] Sample Nos. 47 and 48 were tested by mainly changing the C content and the Cr content of the powder A. Table 9 shows the results.

[0229]

Table 9

[0230]

[0231] According to Table 9, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0232] In particular, compared with sample number 141 in which the content of X2 exceeds 3.00at%, the Isat improvement rates of sample numbers 48, 142 to 150 in which the content of C is between 0at% and 5.00at% and the content of X2 (Cr) is between 0at% and 3.00at% are better. The improvement rate of core loss is better than that of sample number 151 in which the content of C exceeds 5.00at%. It is believed that the Isat improvement rate of sample number 141 is low because the more X2, the easier it is to reduce the magnetic properties, especially the saturation magnetic flux density. It is believed that the improvement rate of core loss of sample number 151 is low because the amorphous nature of powder A is reduced by containing a lot of C, and the magnetic properties of powder A are reduced.

[0233] (Experimental Example 10)

[0234] Sample Nos. 49 and 50 were mainly implemented by changing the content of B and the content of Fe in powder A. Sample Nos. 51 and 52 were mainly implemented by changing the content of B and the content of Si in powder A. Sample Nos. 53 and 54 were mainly implemented by changing the content of B and the content of P in powder A. Sample Nos. 55 and 56 were mainly implemented by changing the content of B, the content of P, and the content of Nb in powder A. The results are shown in Table 10.

[0235]

Table 10

[0236]

[0237] According to Table 10, compared with the comparison example which has essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are substantially improved and the core loss is improved.

[0238] In particular, for sample numbers 50, 52, 54, 56, 161 to 168, 172 to 175, 181 to 185, and 192 to 196, in which the B content is 2.00 at% to 20.00 at%, the P content is 0 at% to 14.00 at%, the Si content is 0 at% to 15.00 at%, and the X3 (Nb) content is 0 at% to 9.00 at%, the improvement rate of the core loss is better than that of sample number 169 in which the B content exceeds 20.00 at% and sample number 186 in which the B content is less than 2.00 at% and the P content exceeds 14.00 at%. The improvement rate of Isat is better than that of sample number 171 in which the Si content exceeds 15.00 at% and sample number 191 in which the X3 content exceeds 9.00 at%. It is believed that the core loss improvement rate of sample numbers 169 and 186 is low because the magnetic properties are reduced due to the reduction of amorphous properties regardless of whether the B content is too much or too little, and even if the P content is too much, the magnetic properties are reduced due to the reduction of saturation flux density. It is believed that the Isat improvement rate of sample number 171 is low because the saturation flux density is reduced by containing a lot of Si, and the magnetic properties are reduced. It is believed that the Isat improvement rate of sample number 191 is low because the Curie point is reduced by containing a lot of X3, the saturation flux density at room temperature is reduced, and the magnetic properties are reduced.

[0239] (Experimental Example 11)

[0240] The comparative examples and samples were substantially the same as the samples except that the powder B was not agglomerated and L50 was too small, and the test was performed mainly by changing the type and / or content of X2 in the powder A. In addition, the sample number 200 did not contain X2, and in the sample numbers 201 to 262, part of the Fe and Co in the sample number 200 was replaced with X2. The results are shown in Tables 11A to 11C.

[0241]

Table 11A

[0242]

[0243]

Table 11B

[0244]

[0245]

Table 11C

[0246]

[0247] According to Tables 11A to 11C, compared to the comparison examples with essentially the same conditions except that L50 is too small due to the failure to agglomerate powder B, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are substantially improved and the core loss is improved.

[0248] (Experimental Example 12)

[0249] The comparative example and sample number 106 were substantially the same as sample number 106 except that L50 was too small because powder B was not agglomerated. The same conditions were used except that X2 (Cr) of powder A was replaced with X3 (Nb). Furthermore, the examples and comparative examples were implemented by changing the type and content of X3 and, along with the change in the content of X3, changing the content of B, the content of P, and the content of Si. The results are shown in Table 12.

[0250]

Table 12

[0251]

[0252] According to Table 12, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0253] In particular, the Isat improvement rates of Sample Nos. 271 to 274, 276 to 279, 281 to 284, 286 to 289, 291 to 294, and 296 to 299, in which the content of X3 is 0 at% to 9.00 at%, are better than those of Sample Nos. 275, 280, 285, 290, 295, and 300, in which the content of X3 is more than 9.00 at%. It is believed that the reason why the Isat improvement rates of Sample Nos. 275, 280, 285, 290, 295, and 300 are low is that the Curie point is lowered by containing a lot of X3, the saturation magnetic flux density at room temperature is lowered, and the magnetic properties are lowered.

[0254] (Experimental Example 13)

[0255] The test was carried out under the same conditions as those of Sample Nos. 1 and 5 except that the composition of the powder B was changed. The results are shown in Table 13.

[0256] In sample numbers 71 and 72, the composition of powder B was set to a composition containing essentially only Co. In sample numbers 73 and 74, the composition of powder B was set to 50.0Fe-50.0Co in atomic ratio. In sample numbers 75 and 76, the composition of powder B was set to 90.0Fe-10.0Si in atomic ratio. In sample numbers 77 and 78, the composition of powder B was set to 20.0Fe-80.0Ni in atomic ratio. It was confirmed by XRD that all powders B of sample numbers 71 to 78 had a structure composed of crystals.

[0257]

Table 13

[0258]

[0259] According to Table 13, compared with the comparison example with essentially the same conditions except that L50 is too small due to not agglomerating powder B, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition and microstructure of powder B are changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0260] (Experimental Example 14)

[0261] The same conditions as those of Sample Nos. 1, 5, 11 to 16 of Experimental Examples 1 and 2 were used except that a portion of Powder B having a volume-based median particle size (D50) of 0.8 μm was replaced with Powder C, wherein Powder C was produced under the same conditions as Powder B except that the volume-based median particle size (D50) was 3 μm. In addition, Powder C did not aggregate unlike Powder B. The results are shown in Table 14.

[0262]

Table 14

[0263]

[0264] According to Table 14, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, even in the embodiment where powder C is used in addition to powder A and powder B, the DC superposition characteristics are sufficiently improved and the core loss is improved by agglomerating powder B to satisfy (2×N50)≤L50≤(0.5×V10+3).

[0265] (Experimental Example 15)

[0266] Sample Nos. 87 to 98, 97a to 97c, and 98a to 98c were run under the same conditions as Sample Nos. 81 and 82 except that the composition and microstructure of the powder C were changed.

[0267] The composition and microstructure of the powder C in sample numbers 87 and 88 were made the same as the composition and microstructure of the powder B in sample numbers 71 and 72. The composition and microstructure of the powder C in sample numbers 89 and 90 were made the same as the composition and microstructure of the powder B in sample numbers 73 and 74. The composition and microstructure of the powder C in sample numbers 91 and 92 were made the same as the composition and microstructure of the powder B in sample numbers 75 and 76. The composition and microstructure of the powder C in sample numbers 93 and 94 were made the same as the composition and microstructure of the powder B in sample numbers 77 and 78.

[0268] The composition and microstructure of the powder C in sample numbers 95 and 96 were made the same as the composition and microstructure of the powder A in sample numbers 45 and 46. The composition and microstructure of the powder C in sample numbers 97 and 98 were made the same as the composition and microstructure of the powder A in sample numbers 47 and 48. The composition and microstructure of the powder C in sample numbers 97a and 98a were made the same as the composition and microstructure of the powder A in sample numbers 51 and 52. The composition and microstructure of the powder C in sample numbers 97b and 98b were made the same as the composition and microstructure of the powder A in sample numbers 53 and 54. The composition and microstructure of the powder C in sample numbers 97c and 98c were made the same as the composition and microstructure of the powder A in sample numbers 55 and 56.

[0269]

Table 15

[0270]

[0271] According to Table 15, compared with the comparison example with essentially the same conditions except that L50 is too small due to not agglomerating powder B, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition and microstructure of powder C are further changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0272] (Experimental Example 16)

[0273] In Experimental Example 16, a powder A, which was mostly large particles, was produced by water atomization. The composition of the powder A was set to be a Fe-Co-BP-Si-Cr system composition. Specifically, in terms of atomic ratio, it was set to be 57.4Fe-24.6Co-11.0B-3.0P-3.0Si-1.0Cr.

[0274] Regarding the conditions of the water atomization method, the pressure of the high-pressure water is set to 50.0 MPa to 200 MPa, and the ejection rate of the molten metal is set to 0.5 kg / min to 4.0 kg / min.

[0275] The classification method of the powder prepared by the water atomization method is described. First, the obtained powder is sieved using a sieve with a mesh size of 250 μm to remove coarse particles. Next, air flow classification is performed to make the median particle size (D50) of powder A based on volume as the target value. An air flow classifier (FACULTY manufactured by Hosokawa Micron Corporation) is used as a classifying device, and the classification rotor speed is set to 4000 rpm or more and 20000 rpm or less to implement air flow classification.

[0276] The same procedure as in Experimental Example 1 was followed except that the atomization conditions and the classification conditions under the airflow classification were appropriately controlled, the median particle size (D50) of the obtained powder A on a volume basis was set to 0.8 μm, the median particle size (D50) of the powder B was set to 0.3 μm, and the content of the epoxy resin was controlled so that the relative magnetic permeability μ of the magnetic core finally obtained was 20. The results are shown in Table 16A.

[0277] The same procedure as in Experimental Example 1 was followed except that the atomization conditions and the classification conditions under the airflow classification were appropriately controlled, the median particle size (D50) of the obtained powder A on a volume basis was set to 3 μm, the median particle size (D50) of the powder B was set to 0.5 μm, and the amount of epoxy resin added was controlled so that the relative magnetic permeability μ of the magnetic core finally obtained was 25. The results are shown in Table 16B.

[0278] Table 16A

[0279]

[0280]

Table 16B

[0281]

[0282] According to Table 16A and Table 16B, in the embodiment where (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even when the median particle sizes of powders A and B are changed, the DC superposition characteristics are sufficiently improved and the core loss is improved compared to the comparative example with substantially the same conditions except that L50 is too small due to not agglomerating powder B. However, the core loss of the comparative example (sample number 314) in which L50 is too large due to excessive agglomeration of powder B is not sufficiently improved compared to sample number 301. The core loss of the comparative example (sample number 334) in which L50 is too large due to excessive agglomeration of powder B is not sufficiently improved compared to sample number 321.

[0283] (Experimental Example 17)

[0284] Regarding Experimental Example 16 and Sample Nos. 321 and 329 in Table 16B, the same conditions were used except that the composition of powder A was changed. Regarding the composition of powder A, the total content ratio of Fe and Co was mainly changed. The results are shown in Table 17. Regarding Experimental Examples 17 to 22, the description of comparative examples with substantially the same conditions as the samples was omitted except that L50 was too small because powder B was not agglomerated.

[0285]

Table 17

[0286]

[0287] According to Table 17, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0288] In particular, the improvement rate of the core loss of sample Nos. 329, 342 to 357, in which the total content of Fe and Co is 70.00 at% or more and 96.00 at% or less, is better than that of sample Nos. 341 and 358, in which the total content of Fe and Co is outside the above range. It is believed that the improvement rate of the core loss of sample No. 341 is low because the soft magnetic properties of powder A are reduced. It is believed that the improvement rate of the core loss of sample No. 358 is low because the amorphous nature of powder A is lower than that of other samples, so the soft magnetic properties of powder A are reduced.

[0289] (Experimental Example 18)

[0290] The comparative example and sample number 346 were run under substantially the same conditions as sample number 346 except that powder B was not agglomerated and L50 was too small, but the contents of Fe, Co, and Ni in powder A were changed. The results are shown in Table 18.

[0291]

Table 18

[0292]

[0293] According to Table 18, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0294] In particular, the improvement rate of the core loss of sample numbers 346, 361 to 365, 367 to 371, 373 to 376, in which the content of Fe is greater than the total content of Co and Ni, is better than that of sample numbers 366, 372, and 377, in which the content of Fe is less than the total content of Co and Ni. It is believed that the improvement rate of the core loss of sample numbers 366, 372, and 377 is low because the soft magnetic properties are lower than those of other samples.

[0295] (Experimental Example 19)

[0296] The same method as sample numbers 47 and 48 was used except that the median particle size of powder A was changed to 3 μm, the median particle size of powder B was changed to 0.5 μm, and the pressure value of powder B was changed. The sample number 388 was a sample that was made in the same way as sample number 48 except that the above conditions were changed.

[0297] Furthermore, the comparative example and sample number 388 were conducted under substantially the same conditions as sample number 388 except that L50 was too small because powder B was not agglomerated, and mainly the C content and Cr content of powder A were changed. The results are shown in Table 19.

[0298]

Table 19

[0299]

[0300] According to Table 19, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0301] In particular, compared with sample number 381 in which the content of X2 exceeds 3.00 at% and sample number 392 in which the content of C exceeds 5.00 at%, the improvement rate of the core loss of sample numbers 382 to 391 in which the content of C is 0 at% to 5.00 at% and the content of X2 (Cr) is 0 at% to 3.00 at% is better. It is believed that the improvement rate of the core loss of sample number 381 is low because the more X2, the easier it is to reduce the soft magnetic properties. It is believed that the improvement rate of the core loss of sample number 392 is low because it contains a lot of C, so the amorphousness is reduced and the soft magnetic properties are reduced.

[0302] (Experimental Example 20)

[0303] The same method as sample numbers 49 and 50 was used except that the median particle size of powder A was changed to 3 μm, the median particle size of powder B was changed to 0.5 μm, and the pressure value of powder B was further changed. The sample that was made in the same way as sample number 50 except that the median particle size of powder A was changed was set as sample number 404. Furthermore, the comparative example and sample number 404, which were substantially the same as sample number 404 except that L50 was too small because powder B was not agglomerated, were mainly made to change the B content and Fe content of powder A. The results are shown in Table 20.

[0304] The same method as sample numbers 51 and 52 was used except that the median particle size of powder A was changed to 3 μm, the median particle size of powder B was changed to 0.5 μm, and the pressure value of powder B was further changed. The sample that was used in the same way as sample number 52 except that the median particle size of powder A was changed was set as sample number 414. Furthermore, the comparative example and sample number 414, which were substantially the same as sample number 414 except that L50 was too small because powder B was not agglomerated, were mainly used to change the B content and Si content of powder A. The results are shown in Table 20.

[0305] The same method as sample numbers 53 and 54 was used except that the median particle size of powder A was changed to 3 μm, the median particle size of powder B was changed to 0.5 μm, and the pressure value of powder B was further changed. The sample that was used in the same way as sample number 54 except that the median particle size of powder A was changed was set as sample number 417. In addition, the comparative example and sample number 417, which were substantially the same as sample number 417 except that L50 was too small because powder B was not agglomerated, were mainly used to change the B content and P content of powder A. The results are shown in Table 20.

[0306] The same method as sample numbers 55 and 56 was used except that the median particle size of powder A was changed to 3 μm, the median particle size of powder B was changed to 0.5 μm, and the pressure value of powder B was further changed. The sample that was used in the same way as sample number 56 except that the median particle size of powder A was changed was set as sample number 427. In addition, the comparative example and sample number 427, which were substantially the same as sample number 427 except that L50 was too small because powder B was not agglomerated, were mainly used to change the B content, P content, and Nb content of powder A. The results are shown in Table 20.

[0307]

Table 20

[0308]

[0309] According to Table 20, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0310] In particular, the improvement rate of core loss in sample numbers 401 to 409, 412 to 422, and 425 to 430, in which the B content is between 2.00 at% and 20.00 at%, the P content is between 0 at% and 14.00 at%, the Si content is between 0 at% and 15.00 at%, and the X3 (Nb) content is between 0 at% and 9.00 at%, is better than that in sample number 410 in which the B content exceeds 20.00 at%, sample number 423 in which the B content is less than 2.00 at% and the P content exceeds 14.00 at%, sample number 411 in which the Si content exceeds 15.00 at%, and sample number 424 in which the X3 content exceeds 9.00 at%. The reason why the improvement rate of the core loss of sample Nos. 410 and 423 is low is that the soft magnetic properties of powder A are reduced due to the reduction of the amorphous nature of powder A, regardless of whether the content of B in powder A is too much or too little. The reason why the improvement rate of the core loss of sample No. 411 is low is that the saturation magnetic flux density of powder A is reduced due to the inclusion of a large amount of Si in powder A, and the soft magnetic properties of powder A are reduced. The reason why the improvement rate of the core loss of sample No. 424 is low is that the Curie point of powder A is reduced due to the inclusion of a large amount of X3 in powder A, and the saturation magnetic flux density of powder A at room temperature is reduced, and the soft magnetic properties are reduced.

[0311] (Experimental Example 21)

[0312] Samples No. 440 to 502 were prepared in the same manner as Samples No. 200 to 262, except that the median particle size of powder A was changed to 3 μm, the median particle size of powder B was changed to 0.5 μm, and the pressurization value of powder B was changed. Furthermore, comparative examples were prepared under substantially the same conditions as the samples, except that L50 was too small because powder B was not agglomerated. Sample No. 440 did not contain X2, and in Samples No. 441 to 502, part of Fe and Co in Sample No. 440 was replaced with X2. The results are shown in Tables 21A to 21C.

[0313]

Table 21A

[0314]

[0315]

Table 21B

[0316]

[0317]

Table 21C

[0318]

[0319] According to Tables 21A to 21C, compared to the comparison example with essentially the same conditions except that L50 is too small due to not agglomerating powder B, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0320] (Experimental Example 22)

[0321] The comparative example and sample number 346 were substantially the same as sample number 346 except that the powder B was not agglomerated and L50 was too small. The same conditions were used except that X2 (Cr) of powder A was replaced with X3 (Nb). Furthermore, the examples and comparative examples were tested by changing the type and content of X3, and the content of B, the content of P, and the content of Si were changed along with the change of the content of X3. The results are shown in Table 22.

[0322]

Table 22

[0323]

[0324] According to Table 22, compared with the comparison example with essentially the same conditions except that L50 is too small because powder B is not agglomerated, in the embodiment in which (2×N50)≤L50≤(0.5×V10+3) is satisfied by agglomerating powder B even if the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.

[0325] In particular, the improvement rate of the core loss of the samples Nos. 511 to 514, 516 to 519, 521 to 524, 526 to 529, 531 to 534, 536 to 539, which have an X3 content of 0 to 9.00 at%, is better than that of the samples Nos. 515, 520, 525, 530, 535, and 540, which have an X3 content of more than 9.00 at%. It is believed that the reason why the improvement rate of the core loss of the samples Nos. 515, 520, 525, 530, 535, and 540 is low is that the powder A contains a lot of X3, so that the Curie point of the powder A is lowered, the saturation magnetic flux density of the powder A at room temperature is lowered, and the soft magnetic properties are lowered.

[0326] The soft magnetic particles contained in the magnetic cores of the samples obtained in Experimental Examples 1 to 22 were confirmed to have fine structures by electron diffraction patterns obtained by TEM. It was confirmed that the fine structures of the soft magnetic particles derived from powder A, the soft magnetic particles derived from powder B, and the soft magnetic particles derived from powder C did not substantially change before and after molding.

Claims

1. A magnetic core, wherein: The magnetic core contains soft magnetic particles. When the value of D10 in the particle size distribution of the soft magnetic particles based on volume is set to V10; the value of D50 in the particle size distribution of the soft magnetic particles based on volume is set to V50; the value of D50 in the particle size distribution of the soft magnetic particles based on number is set to N50, and the unit of the particle size distribution is μm, The soft magnetic particles include large particles with a particle size of 0.5×V50 or more and small particles with a particle size of 2×N50 or less. When the distance from a certain small particle to the largest particle closest to the small particle is set as L, and the median value of L calculated for all small particles is set as L50, Satisfies: 2×N50≤L50≤0.5×V10+3.

0.

2. The magnetic core according to claim 1, wherein: At least a portion of the soft magnetic particles has a composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f express, X1 is one or more selected from Co and Ni, X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements, X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W, Satisfies 0≤p≤0.5, 2.00≤a≤20.00、 0.00≤b≤14.00、 0.00≤c≤15.00、 0.00≤d≤5.00、 0.00≤e≤3.00、 0.00≤f≤9.00, and 70.00≤100-(a+b+c+d+e+f)≤96.

00.

3. The magnetic core according to claim 1 or 2, wherein: V10 is 3.0 μm or more and 20.0 μm or less.

4. The magnetic core according to claim 1 or 2, wherein: V50 is 8.0 μm or more and 40.0 μm or less.

5. The magnetic core according to claim 1 or 2, wherein: At least a part of the soft magnetic particles contains Fe, Co and / or Ni.

6. A magnetic core, wherein: The magnetic core contains soft magnetic particles. When the value of D10 in the particle size distribution of the soft magnetic particles based on volume is set to V10; the value of D50 in the particle size distribution of the soft magnetic particles based on volume is set to V50; and the value of D50 in the particle size distribution of the soft magnetic particles based on number is set to N50, The soft magnetic particles include large particles with a particle size of 0.5×V50 or more and small particles with a particle size of 2×N50 or less. When the distance from a certain small particle to the largest particle closest to the small particle is set as L, and the median value of L calculated for all small particles is set as L50, Satisfies: 2×N50≤L50≤0.5×V10.

7. The magnetic core according to claim 6, wherein: At least a portion of the soft magnetic particles has a composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f express, X1 is one or more selected from Co and Ni, X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements, X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W, Satisfies 0≤p≤0.5, 2.00≤a≤20.00、 0.00≤b≤14.00、 0.00≤c≤15.00、 0.00≤d≤5.00、 0.00≤e≤3.00、 0.00≤f≤9.00, and 70.00≤100-(a+b+c+d+e+f)≤96.

00.

8. The magnetic core according to claim 6 or 7, wherein: V10 is 3.0 μm or more and 20.0 μm or less.

9. The magnetic core according to claim 6 or 7, wherein: V50 is 8.0 μm or more and 40.0 μm or less.

10. The magnetic core according to claim 6 or 7, wherein: At least a part of the soft magnetic particles contains Fe, Co and / or Ni.

11. A magnetic component, wherein: A magnetic core comprising the magnetic core according to any one of claims 1 to 10.

12. An electronic device, wherein: A magnetic core comprising the magnetic core according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Odakusuino jokasochi

    JP1976010660A

  • Coil encapsulating magnetic component and method of manufacturing the same

    JP2003309024A

  • Composite magnetic material, core using the same, and magnetic element

    JP2004197218A

  • Complex magnetic material and method for manufacturing inductor using the same

    JP2004363466A